Supporting casual teaching staff in the Australian neoliberal university: A collaborative approach (Journal of Applied Learning and Teaching, 2021)
In this paper, we argue for a collaborative approach to online education as a corrective to many of the challenges of contemporary tertiary teaching. The recent intensification in online teaching due to the COVID-19 pandemic suggests that articulating an effective model of online teaching is judicious. While the model we propose is apposite for all teaching staff, we focus on its benefits for casual staff due to their increasing share of teaching responsibility yet limited access to institutional support. Using a collaborative auto-ethnographic framework, we analysed reflections from past and present members of our teaching team. We contend that collaborative teaching counters teachers’ typical experience of isolation and facilitates personal and professional learning. By providing institutional support for regular productive interactions, staff wellbeing is promoted, and the precariousness of contemporary university teaching is reduced. These aspects of collaborative teaching speak to its sustainability both for staff and the institution. We conclude that it is in the university sector’s best interest to implement similar collaborative teaching models.